2009
DOI: 10.1210/jc.2009-0425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Exon 3-Deleted Growth Hormone (GH) Receptor Polymorphism on Baseline Height and the Growth Response to Recombinant Human GH Therapy in GH-Deficient (GHD) and Non-GHD Children with Short Stature: A Systematic Review and Meta-Analysis

Abstract: This meta-analysis in prepubertal children with short stature indicates that GHR(d3) is associated with increased baseline height in GHD, but not in non-GHD. Furthermore, GHR(d3) stimulates growth velocity by an additional effect of approximately 0.5 cm during the first year of rhGH treatment, and this effect is more pronounced at lower doses of rhGH and higher age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 25 publications
3
78
0
7
Order By: Relevance
“…47,48 This latter polymorphism was not found to be significantly more frequent in pygmies than in non-pygmies.…”
Section: Resultsmentioning
confidence: 74%
“…47,48 This latter polymorphism was not found to be significantly more frequent in pygmies than in non-pygmies.…”
Section: Resultsmentioning
confidence: 74%
“…The d3-GHR has been suggested to confer a more GH-sensitive receptor, and in GHD short children carriers of the d3-allele have in many studies, although not all, been shown to respond better to GH in terms of growth velocity and final height than noncarriers (7). Studies on adult GHD populations have produced more conflicting data, showing either no association or a better response in carriers of the d3-GHR (8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, growth response during the first year of rhGH therapy, expressed both as height SDS gain and as growth velocity, was significantly increased in prepubertal non-GHD and GHD short children bearing the d3-GHR genotype in comparison with the fl-GHR genotype. The meta-analysis found that the presence of d3-GHR allele stimulated growth velocity by an additional effect of approximately 0.5 cm during the first year of rhGH treatment, and such effect was more pronounced at lower rhGH doses and in children of higher age (30).…”
Section: Ghr Polymorphism In Short Childrenmentioning
confidence: 98%
“…Wassenaar et al (30) conducted a systematic review and meta-analysis of 15 studies published between 2004 and 2008, with a range of 28-240 patients included in the series, aiming at assessing the effects of d3-GHR on baseline height and the first year's growth response to rhGH treatment in prepubertal short GHD children (7 studies) and non-GHD children (6 studies in small for gestational age (SGA), 3 studies in idiopathic short stature (ISS) and 2 studies in Turner syndrome). The meta-analysis showed that d3-GHR was associated with increased baseline height in GHD prepubertal children with short stature, but not in non-GHD children.…”
Section: Ghr Polymorphism In Short Childrenmentioning
confidence: 99%
See 1 more Smart Citation